Patients with schizophrenia are less prone to interpret virtual others' empathetic questioning as helpful. (30th August 2016) - Berrada-Baby, Zina; Oker, Ali; Courgeon, Matthieu; Urbach, Mathieu; Bazin, Nadine; Amorim, Michel-Ange; Martin, Jean-Claude; Passerieux, Christine; Roux, Paul; Brunet-Gouet, Eric
Abstract: Individuals with schizophrenia are impaired in their neurocognition and present cognitive biases. These impairments may lead to a deficit in recognizing helping intentions of others. To investigate recognition of help, we designed a card-guessing game (Virtual Help Recognition Paradigm) involving two successive virtual agents asking questions to the participant at different moments of the game. These questions were either empathetic (i.e. on the subject's feelings) or non-empathetic (i.e. on technical aspects of the game). We assessed how much the participant felt that the virtual agent had helped him and, her attitude and personality traits. We measured how much the participant trusted the virtual agent with a monetary allocation procedure. Twenty individuals with schizophrenia and twenty healthy controls were recruited. The controls' ratings demonstrated that they interpreted empathetic questioning as helping and rewarded it positively with an increased monetary allocation. Participants with schizophrenia had a reduced perception of the differences between the two agents. Only the rating concerning the "interest/attention" of the agent toward these participants yielded significant differences among conditions. Hypothetically, individuals with schizophrenia take into account the fact they are the object of another's attention, but may fail to infer a helping intention and to behave accordingly. Highlights: Virtual agents were used to generate empathetic versus nonempathetic situations. Healthy subjects were able to detect empathy, helping intention. Patients with schizophrenia had impoverished recognition of helping intention.